1996
DOI: 10.1038/nbt0396-309
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibodies with Sub-nanomolar Affinities Isolated from a Large Non-immunized Phage Display Library

Abstract: To generate a stable resource from which high affinity human antibodies to any given antigen can be rapidly isolated, functional V-gene segments from 43 non-immunized human donors were used to construct a repertoire of 1.4 x 10(10) single-chain Fv (scFv) fragments displayed on the surface of phage. Fragments were cloned in a phagemid vector, enabling both phage displayed and soluble scFv to be produced without subcloning. A hexahistidine tag has been incorporated to allow rapid purification of scFv by nickel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
631
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 952 publications
(653 citation statements)
references
References 42 publications
13
631
0
5
Order By: Relevance
“…The results (not shown) demonstrated that at least 60% percent, and probably more, of the randomly picked clones were efficiently displayed using the phage production methods described in the Materials and Methods. This value is similar or better to those reported for human scFv libraries (Vaughan et al, 1996;O'Connell et al, 2002). The failure to observe scFv/pIII fusion proteins in some clones is likely caused by the poor expression levels of these scFv fusions, or by aberrant or introduced stop codons.…”
Section: Rat Scfv Primer Design and V-domain Amplificationsupporting
confidence: 86%
“…The results (not shown) demonstrated that at least 60% percent, and probably more, of the randomly picked clones were efficiently displayed using the phage production methods described in the Materials and Methods. This value is similar or better to those reported for human scFv libraries (Vaughan et al, 1996;O'Connell et al, 2002). The failure to observe scFv/pIII fusion proteins in some clones is likely caused by the poor expression levels of these scFv fusions, or by aberrant or introduced stop codons.…”
Section: Rat Scfv Primer Design and V-domain Amplificationsupporting
confidence: 86%
“…To neutralize the inhibitory activity of CRP and to potentiate complement-mediated killing of B lymphoma cells, we have isolated scFv to CD55 and CD59 from a human phage-display library [18] to be used in combination with complement-fixing Rituximab and other complement-activating mAb. The human phage Ab libraries offer the advantage over conventional mAb of a large Ab repertoire that is not shaped by the constraints of the immune system, with a dramatic increase in the chances of isolating Ab to selfantigens [20]. On the other hand, the Ab currently used in cancer therapy, unlike human scFv, are of murine origin and, although engineered to become chimeric or humanized, they still contain murine variable portions of the original Ig that may elicit an anti-idiotypic response [21,22] resulting in their rapid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Human soluble extracellular domain (ECD) TRAIL-R1-flag fusion protein at 10 mg ml À1 in PBS was immobilised onto immunotubes (Nunc, Rochester, NY, USA) overnight at 41C. Three or four rounds of panning selections were performed using the scFv human antibody phage library with approximately 1.4 Â 10 10 individual recombinants (Vaughan et al, 1996). A deselection round was performed on an irrelevant fusion protein to remove any nonspecific binders.…”
Section: Selection and Generation Of A Trail-r1 Agonist Monoclonal Anmentioning
confidence: 99%